Chapter Le comunità energetiche per l'autoriproduzione della bioregione - Bolognesi, Monica (Territori, 2023)
The essay outlines the features of an eco-territorialist and patrimonial approach to energy transition, a process that is not taking place with the necessary urgency nor with the desirable consistency with respect to the principles of ecologic-environmental and landscape sustainability. Energy resources, one of the founding components of the urban bioregion, are available in every territory with specific peculiarities; rethinking the energy system in a non-predatory perspective means protecting the reproducibility of such resources and establishing virtuous dynamics creating territorial value added. Energy communities can represent effective tools for the enhancement of local energy heritages still not properly employed, towards a horizon of progressive energy sovereignty of territories.